The CaSBP11 gene functions as a negative regulator in pepper drought stress - Zhang, Huai-Xia; Zhang, Yuan; Zhang, Bo-Wen; Pan, Fei-Fei (Frontiers in Plant Science, 2025)
The SBP-box gene family, an exclusively plant transcription factor, is critical for plant growth, development, and adaptive responses to both biotic and abiotic stresses. However, its role under non-biological stresses, specifically drought, remains overlooked in pepper plants. In our previous work, we isolated an SBP-box gene, CaSBP11, from the pepper genomic database. Subsequently, we employed virus-induced gene silencing, overexpression, and protein interaction experiments to investigate the function of CaSBP11 under drought stress. Our results revealed that drought conditions significantly upregulated CaSBP11 expression, whereas ABA treatment suppressed it. Silencing CaSBP11 enhanced drought resistance in pepper, with increased stomatal aperture and ABA levels, and reduced stomatal density, water loss rates, and reactive oxygen species (ROS) accumulation compared to control plants. Conversely, overexpression of CaSBP11 in Nicotiana benthamiana decreased drought tolerance, with CaSBP11-overexpressing plants showing reduced ABA sensitivity, lower stomatal aperture and ABA levels, and increased stomatal density and ROS production compared to wild-type plants. Interestingly, under non-stress conditions, core ABA signaling genes (CaPP2C, CaPYL9, CaSNRK2.4, CaAREB) exhibited lower expression in CaSBP11-silenced plants compared to controls, whereas this trend was reversed in CaSBP11-overexpressing lines (NbPP2C, NbAREB, NbSNRK2.4, NbSRK2E). Additionally, CaSBP11 was found to interact with CaPP2C, CaPYL9, CaSNRK2.4, and CaAREB in nucleus. These data suggest that CaSBP11 negatively regulates plant responses to drought stress and may interact with these key genes in the ABA signaling pathway to mediate this response.